SOSIALISASI PENGOLAHAN LIMBAH ORGANIK SEBAGAI ECO ENZYME PADA KELOMPOK TANI KELURAHAN BHAKTI KARYA - Sitompul, Hamela Sari; As’ad, Octasella Ainani; Nasution, Nurhadida; Yanti , Mariana Eva; Mulia, Sukri; Surbakti, Supriadi; Yurizky, Yusra (Jurnal Inovasi Pengabdian Masyarakat, 2024)
Organic waste is a type of waste that can weather or decompose into smaller materials, while non-organic waste is a type of waste that is very difficult to decompose. Binjai is one of the villages in Deli Serdang which is not free from waste management problems. In this case, Deli Serdang district produces household waste (SRT) and similar household waste (SSRT) in quite large quantities. The objectives of this activity are: (1) To provide information and education about processing organic waste into eco enzymes; (2) Provide information about the processing and use of Eco Enzyme in agriculture as organic fertilizer. The target of the activity was farmer groups in Bhakti Karya Village, Binjai City on January 17 2024. The activity was carried out twice using two methods, namely lecture, demonstration and question and answer. The service activity began with the team making eco-enzyme samples. The purpose of making samples is for harvesting while making eco-enzyme takes three months. Based on the results of the community service activities that have been carried out, it can be concluded that the socialization of making eco-enzymes can meet the needs and provide benefits to the Bhakti Karya sub-district farmer group, so that this service can really be continued